Endothelin receptor antagonism during preeclampsia: a matter of timing?. (20th June 2019) - Hitzerd, Emilie; Neuman, Rugina I.; Mirabito Colafella, Katrina M.; Reiss, Irwin K.M.; van den Meiracker, Anton H.; Danser, A.H. Jan; Visser, Willy; Versmissen, Jorie; Saleh, Langeza
Abstract : Preeclampsia (PE) is a pregnancy complication, featuring elevated blood pressure and proteinuria, with no appropriate treatment. Activation of the endothelin system has emerged as an important pathway in PE pathophysiology based on experimental PE models where endothelin receptor antagonists (ERAs) prevented or attenuated hypertension and proteinuria. Hence, ERAs have been suggested as potential therapy for PE. However, developmental toxicity studies in animals have shown severe teratogenic effects of ERAs, particularly craniofacial malformations. Nonetheless, sporadic cases of pregnancy in women using ERAs to treat pulmonary hypertension have been described. In this review we give an overview of cases describing ERA use in pregnancy and critically address their possible teratogenic effects. A systematic search in literature yielded 18 articles describing 39 cases with ERA exposure during human pregnancy. In most cases there was only exposure in the first trimester, but exposure later or throughout pregnancy was reported in five cases. Elective termination of pregnancy was performed in 12 pregnancies (31%), two ended in a spontaneous miscarriage (5%) and no fetal congenital abnormalities have been described in the remaining cases. These preliminary findings support the idea that ERA treatment for severe, early onset PE might be an option if applied later in pregnancy, when organogenesis is completed to avoid teratogenic risks. However, third trimester toxicology studies are warranted to evaluate drug safety. Subsequently, it remains to be established whether ERA treatment is effective for alleviating maternal symptoms, as demonstrated in preclinical PE models, allowing pregnancy prolongation without leading to adverse neonatal outcomes.